Nursing Interventions for Bone Healing After Open Reduction and Internal Fixation: A Scoping Review - Faisal Abda’u; Kumboyono Kumboyono; Laily Yuliatun (MEDICA (International Medical Scientific Journal), 2026)
Nursing care plays an important role in supporting postoperative recovery and optimizing clinical outcomes in patients undergoing Open Reduction and Internal Fixation (ORIF). However, nursing interventions that support bone healing in this population have not been comprehensively mapped. This scoping review aimed to identify and map nursing interventions that support bone healing and postoperative recovery in patients undergoing ORIF. Literature searches were conducted in PubMed, ScienceDirect, ProQuest, and Google Scholar using keywords based on the Population–Concept–Context (PCC) framework for studies published between 2015 and 2025. Article screening and selection were conducted using predefined inclusion and exclusion criteria in accordance with the PRISMA-ScR guidelines. Data from the included studies were extracted, categorized, and synthesized thematically. A total of 20 studies were included in this review. The findings demonstrated that nursing interventions could be classified into four major domains: observational, therapeutic, educational, and collaborative interventions. Frequently reported interventions included pain management, early mobilization and rehabilitation support, clinical monitoring, health education, discharge planning, nutritional support, and multidisciplinary collaboration. The reviewed studies suggested that these interventions were associated with improved postoperative clinical outcomes, including reduced pain and complications, enhanced mobility and functional recovery, improved self-care ability, and better quality of life. However, most studies evaluated indirect clinical outcomes rather than direct radiographic indicators of bone healing. Further research is needed to evaluate the effectiveness of specific nursing interventions on radiographic bone healing outcomes across different fracture types and patient populations.